Prevalence and Drivers of COVID-19 Vaccine Booster Hesitancy Among German University Students and Employees - Attia, Sameh; Mausbach, Katharina; Klugar, Miloslav; Howaldt, Hans-Peter; Riad, Abanoub (Frontiers in public health, 2022)
COVID-19 booster hesitancy (VBH) is a serious public health challenge which acts simultaneously with the waning vaccine-elicited immunity and the emerging viral variants to prolong the pandemic interval. Therefore, this study aimed to evaluate the prevalence of COVID-19 VBH among a highly educated subset of the German population and to explore the potential demographic, anamnestic, and psychosocial determinants of this problem. A cross-sectional survey-based study was conducted in December 2021 among German university students and employees to evaluate their attitudes toward COVID-19 vaccine booster (VB) doses. The study used a self-administered questionnaire that was developed and disseminated digitally, and the questionnaire inquired about participants' demographic characteristics, COVID-19-related anamnesis, COVID-19 vaccine-related anamnesis, and psychosocial predictors of COVID-19 VBH. A total of 930 participants were recruited, of which 608 (65.4%) were students, 682 (73.3%) were females, and their mean age was 29.08 ± 10.93 years. Fifty-five participants (5.9%) had been previously infected by COVID-19 and the vast majority of infections happened before the first vaccine dose. Over 95% of the participants had received at least one vaccine dose, and the most commonly administered vaccine was BNT162b2. The overall COVID-19 VB acceptance was satisfactory (87.8%) and induced by various altruistic promoters, e.g., family health protection, community health protection, and patients' health protection. The students (86.3%), the previously infected participants (76.4%), the participants who did not receive primer doses of COVID-19 vaccines (2.5 %), and those who were hospitalized (40%) and sought medical care/treatment after receiving primer doses (86.8%) were less likely to accept COVID-19 VB compared to the employees (90.7%), the participants who were not previously infected (88.6%) and those who received primer dose (91.7%), and the participants who were not hospitalized (92%) nor sought medical care/treatment after primer doses (92.9%), respectively. The perceived effectiveness of COVID-19 VB against severe illness (adjusted odds ratio "AOR": 47.65-95% confidence interval "CI": 23.65-96.49), symptomatic infection (AOR: 9.87-95% CI: 5.20-18.71), community transmission (AOR: 5.34-95% CI: 3.00-9.49) and emerging variants (AOR: 19.12-95% CI: 10.57-34.55) were key predictors for COVID-19 VB acceptance; therefore, it needs to be highlighted in vaccine messaging. In addition, the perceived safety of COVID-19 VB and ethical dilemmas of vaccine justice need to be addressed publicly.
Keywords: Young Adult; COVID-19 vaccines; Cross-Sectional Studies; studenti; Male; vakcíny; cross-sectional studies; Immunization, Secondary; mladý dospělý; Adolescent; decision making; Adult; vakcíny proti COVID-19; prevalence; vakcína BNT162; dospělí; mužské pohlaví; social determinants of health; SARS-CoV-2; mladiství; Germany; sekundární imunizace; lidé; Vaccines; ženské pohlaví; Students; Humans; Prevalence; průřezové studie; BNT162 Vaccine; COVID-19 Vaccines; Universities; univerzity; Female; vaccination hesitancy; COVID-19